Reducing Multidimensional Poverty of Elderly: The Role of the New Rural Pension Scheme in China - Yaqian Hu; Hao Han; Pei Liu (Discrete Dynamics in Nature and Society)
Poverty is a multidimensional concept. Besides income, it also includes many nonmonetary dimensions, such as education, health, housing, and access to public goods. Applying a nationally representative survey dataset, this study mainly investigates the role of China’s New Rural Pension Scheme (NRPS) in reducing multidimensional poverty among the rural elderly. We first select four dimensions of life quality, health, social inclusion, and subjective welfare to construct multidimensional poverty indicators. We then divide the sample into two parts by age (45–59 and above 60) and evaluate the poverty-reduction effects of participating behaviors and receiving behavior separately. Moreover, we use the insured subsample to investigate the dynamic influence from insured status on received status. The results showed that, for the 45–59 age group, NRPS participation helped reduce poverty across the given indicators, especially in terms of health, life, and subjective welfare. For the elderly (over 60), receiving the pension effectively reduced poverty. In addition, we found that as age increases, pension income can effectively alleviate the insured subgroup’s multidimensional experience of poverty.